RETRACTED: Ensuring the environmental development of the far east - Blazhevich Oleg; Burkaltseva Diana; Polskaya Svetlana; Osmanova Elnara; Fomin Mikhail; Fomin Alexey; Guk Olga; Bondarenko Daniil (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001